Synthesis and Antibacterial Activity Test of Dibutyl Tin (IV) N-Ethylbenzyl Dithiocarbamate Compound Against Salmonella Thy.Atcc.14028 and Propionibacterium acnes Bacteria - Mukhlis Sanuddin; Medi Andriani; Tiara Angraini (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
The complex compound dithiocarbamate exhibits various biological activities, including anticancer, antibacterial, antifungal, and antioxidant properties. Dibutyl tin (IV) N-ethyl benzyl dithiocarbamate was synthesized to overview its structure and evaluate its antibacterial activity against Salmonella typhimurium ATCC 14028 and Propionibacterium acnes. This compound was synthesized via an in situ method by adding dibutyl tin (IV) dichloride, N-ethylbenzylamine, and carbon disulfide, forming a precipitate, which was then dried to yield a white powder. This powder can also be crystallized. The compound was characterized using FTIR, 1H NMR, and 13C NMR spectroscopy, along with antibacterial activity testing using the disc diffusion method. The FTIR analysis revealed characteristic absorption bands at 1111.00 cm-1 (C-N), 731.02 cm-1 (C-S), 2954.95 cm-1 (C-H), 1602.85 cm-1 (C=C), 360.69 cm-1 (Sn-S), and 567.07 cm-1 (Sn-C). The 1H NMR spectrum showed chemical shifts at 0-3.8570 ppm (δ CH3), 5.0032-5.1472 ppm (δ N-CH2), and 7.2780-7.3607 ppm (δ C6H5). The 13C NMR spectrum displayed signals at 0-34.5610 ppm (δ CH3), 48.6398-56.9247 ppm (δ N-CH2), 127.6651-135.7665 ppm (δ C6H5), and 201.7568 ppm (δ CS2). The antibacterial activity of dibutyl tin (IV) N-ethyl benzyl dithiocarbamate was assessed, revealing inhibition zones against Salmonella typhi of 6.78 mm (100 ppm), 7.36 mm (120 ppm), and 7.76 mm (140 ppm), categorizing the activity as moderate. Against Propionibacterium acnes, inhibition zones were 1.8 mm (100 ppm), 1.88 mm (120 ppm), and 2.13 mm (140 ppm), categorizing the activity as weak. Based on these findings, it can be concluded that dibutyl tin (IV) N-ethyl benzyl dithiocarbamate can be synthesized to form an octahedral structure and exhibits antibacterial activity. However, it is not yet suitable for use as a new antibiotic.